Focusing of visual attention at rest and under physical load in soccer players - Pesce, C.; Tessitore, A.; Casella, R.; Pirritano, M.; Capranica, L. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Introduction In soccer, an important factor of cognitive performance is the ability to optimally allocate attention in the visual field in order to process relevant information under high time pressure (Williams & Davids, 1998). Such attentional demands are coupled with high levels of concomitant physical effort. Sub-maximal physical loads seem to exert positive effects on cognitive performances, probably due to the mediating role of enhanced arousal and resource allocation (Brisswalter et al., 2002). The aim of the present study was to investigate the effects of a concomitant physical load on visual attentional focusing in high-level soccer players. Methods Focusing of visual attention with and without sub-maximal physical load (60% VO2max) was investigated on cycloergometer in 24 high-level soccer players and 24 non-athletes (aged 18-23) by means of an attentional test which measured discrimination reaction times (RTs) to target stimuli. Spatial cueing with cues of different size preceded the presentation of compound stimuli containing the target stimulus at local or global level (e.g., a global "H" letter composed from local "E" and "F" letters). In two separate experiments, task difficulty was varied by manipulating the probability that cue and target matched in size. ANOVA was performed on median RTs. Factors were: group (soccer players vs. non-athletes), physical load (rest vs. workload), cue size (large vs. small), target level (global vs. local). Results In the easier task, only non-athletes had faster RT during exercise than at rest (470 vs. 598 ms), whereas in the more difficult task, also soccer players speeded up RT from the rest to the workload condition (498 vs. 548 ms). In both tasks, soccer players were slower in discriminating local targets and faster in discriminating global targets (561 vs. 533 ms), whereas the reverse was true for non-athletes (518 vs. 550 ms). Such group difference in global/local processing speed was due to the fact that after invalid cueing, soccer players payed higher RT costs to switch from global to local attending, whereas non-athletes payed higher RT costs for the reverse local-to-global attending switch (Fig. 1). Under physical effort, such RT costs of invalid cueing were reduced on both tasks for non-athletes, but only on the more difficult task for soccer players (Fig. 1 right). Discussion/Conclusion The present results suggest: (1) in soccer players, the facilitation effect of physical load on reaction speed seems to be specifically mediated by enhanced processing resources which are exploited for coping with difficult task demands. (2) In contrast to non-athletes, soccer players are better able to attend to global than to local visual information. (3) Such effect is of an attentional nature, since in contrast to non-athletes, soccer players have lower RT costs for enlarging attention than for narrowing it. Expert soccer players might have developed the ability to cope more efficiently with broad attending demands, which are typical of their field activity, and to selectively profit, under difficult attending conditions, from the enhanced resources that are endered available under physical load.